Robert Nozick’s Libertarian Framework of Distributive/Economic Justice: A Critical Assessment of Its Prospects for Providing Global Distributive Justice (Pakistan Business Review, 2021)
This paper addresses a primary disjuncture between the capitalist business and capitalist state. Whereas capitalist business has gone global capitalist state remains national. This paper contends that this disjuncture accounts for the absence of provision of global capitalist distributive/economic justice. Within the framework of Robert Nozick’s entitlement theory of justice, it investigates whether a minimal state can be spontaneously evolved from anarchy providing distributive/economic justice within national borders, and whether a minimal state can ultimately lead to the emergence of a global minimal state providing global distributive/economic justice. This paper argues that a framework for the provision of global distributive/economic justice cannot be developed on the basis of Nozick’s entitlement theory of justice primarily because of problems of Nozickian rectification of past injustices, and disjuncture between national minimal state and an imagined global minimal state.